The mediating role of physical activity attitude in the relationship between physical literacy and a sustainable healthy lifestyle in adolescents - İlbak, İsmail and Akarsu, Mehmet and Cepicka, Ladislav and Valach, Petr (Frontiers in Psychology, 2025)
Background and aimThe sustainability of individuals’ health is not solely dependent on medical interventions but also on the adoption of healthy lifestyle behaviors. The aim of this study was to examine the effect of physical literacy on sustainable healthy lifestyle behaviors in adolescents and to investigate the mediating role of physical activity attitude in this relationship.MethodsPhysical literacy was defined as the independent variable, sustainable healthy lifestyle as the dependent variable, and physical activity attitude as the mediator. Data were collected from a total of 750 voluntary participants (mean age = 15.71 ± 0.99) using the Perceived Physical Literacy Instrument for Adolescents (PPLI), the Lifestyle of Health and Sustainability Scale (LOHAS), and the Youth Physical Activity Attitude Scale (YPAAS). The total score and subscale interpretations of these instruments were considered in the analyses. Ethical approval was obtained, and informed consent was secured from guardians, as well as assent from the adolescents. Data were analyzed using correlation, regression, and structural equation modeling (SEM), with a significance threshold set at p < 0.05.ResultsThe findings revealed a significant and positive relationship between physical literacy and a sustainable healthy lifestyle (r = 0.484, p < 0.001). Physical activity attitude was also significantly correlated with both physical literacy (r = 0.447, p < 0.001) and sustainable healthy lifestyle (r = 0.400, p < 0.001). SEM results indicated that physical literacy directly (β = 0.519) and indirectly (β = 0.139) through physical activity attitude significantly influenced sustainable healthy lifestyle behaviors. The model explained 28% (R2 = 0.28) of the variance in sustainable healthy lifestyle behaviors.ConclusionThese results highlight that physical activity attitude plays a partial mediating role in the relationship and demonstrate that physical literacy is not merely a cognitive or skill-based construct, but a comprehensive competency that shapes adolescents’ attitudes and behaviors. Accordingly, education and health policies aimed at promoting physical literacy should be supported by holistic strategies that also target attitude transformation. The findings contribute to the theoretical literature and highlight the importance of multifaceted intervention models in promoting healthy lifestyle behaviors among adolescents.